2020
DOI: 10.1002/jsfa.10918
|View full text |Cite
|
Sign up to set email alerts
|

Addition of chickpea markedly increases the indigestible carbohydrate content in semolina pasta as eaten

Abstract: BACKGROUND There is a growing interest in increasing dietary fiber (DF) consumption because of the health benefits associated with this nutrient. Pulses are considered a good source of non‐digestible carbohydrates. The aim of this study was to investigate the possibility of substituting semolina with chickpea flour to increase indigestible carbohydrate content without altering the texture of the pasta. RESULTS Pasta was prepared by extruding semolina–chickpea blends. The protein and DF content in the cooked pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
(49 reference statements)
2
7
0
Order By: Relevance
“…Polar amino acids) with increased protein could be responsible for the rising WAC. Increased WAC due to rising fibre is reported byGarcia-Valle et al (2021a) which is in accordance with our study.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Polar amino acids) with increased protein could be responsible for the rising WAC. Increased WAC due to rising fibre is reported byGarcia-Valle et al (2021a) which is in accordance with our study.…”
supporting
confidence: 93%
“…The information presented in Table 1 demonstrated that barley pasta exhibited the longest optimum cooking time (OCT) (6.01 min), which decreased from 5.48 to 5.09 min as chickpea substitution increased from 10% to 40%. The shorter OCT of chickpea substituted pasta can be related to the pasta's center absorbing more water due to a relatively weak–protein–starch network (El‐Sohaimy et al ., 2020; Garcia‐Valle et al ., 2021a). A slight increase in swelling power was observed with increased chickpea content and can be attributed to the degree to which the internal structure of the starch was exposed for action of water (Ritika et al ., 2016).…”
Section: Resultsmentioning
confidence: 99%
“…RS2 increased more total dietary fibers than unripe plantain flour in uncooked spaghetti, while made similar performances in lowering GI, consequently transferring spaghetti into medium GI food. [ 141 ] It is strongly demonstrated that unripe plantain flour is an alternative dietary fiber to RS, and the similar functions were also found in chickpea, [ 142 ] cassava and banana flour. [ 143 ]…”
Section: Food Applicationmentioning
confidence: 97%
“…However, in pasta products, adding chickpea limits the amount of starch gelatinization to an appropriate amount allowing a higher dietary fiber content to match nutritional recommendations (Garcia‐Valle et al., 2020).…”
Section: Technology In the Production Of Chickpea Snacksmentioning
confidence: 99%